Failure Risks of Bracing Treatment in Adolescent Idiopathic Scoliosis - Wei-Siang Fang; Ting-Kuo Chang (Formosan Journal of Musculoskeletal Disorders)
Background: Bracing therapy in adolescent idiopathic scoliosis (AIS) patients has been proven to have about a 70% successful rate of preventing patients from further surgery. While still, about 30% of patients failed and required further surgical intervention. Objectives: To distinguish the difference between the success and failure groups and correct the adjustable risks, this study aimed to investigate the possible risk factors of bracing treatment failure. Materials and Methods: Patients who visited Mackay Hospital during 2017–2022 with a diagnosis of AIS received bracing treatment and were observed and analyzed. Cobb’s angle progressed to >40° was regarded as treatment failure; Cobb’s angle <40° when achieved skeletal maturity was regarded as treatment success. Scoliosis types were evaluated with Lenke classification. Evaluation characteristics include age, gender, body mass index (BMI), body height, brace type, and brace-wearing time. Results: Thirty-nine patients were evaluated until they achieved skeletal maturity. The success rate of brace treatment was 71.8% (28 out of 39 patients), while 18.2% of patients (11 out of 39) experienced treatment failure. A significant difference was noted in initial body height, growth, and BMI. The bracing success group had an average body height of 152.1 and an average growth of 5.75 cm; Patients in the bracing failure group had an average body height of 137.0 and an average growth of 16.84 cm. Patients in the bracing success group had average BMI = 17.8 (kg/m2); Patients in the bracing failure group had average BMI = 15.5 (kg/m2). When analyzed using the Lenke classification, Lenke type 1, 3, and 5 exhibited success rates of 55.6% (5 out of 9), 72.7% (8 out of 11), and 83.3% (14 out of 17), respectively. Patients with main thoracic involvement had higher risks of curve progression to ≥40° (38.1%, 8/21) compared to the main lumbar involvement (16.6%, 3/18). Although no significant difference, the failure group averaged less brace-wearing time at 16.7 h compared to the success group at 18 h. Conclusions: AIS patients with thoracic involvement, with >30° Cobb’s angle, with low BMI, and with less body height without bone maturity might have a higher failure rate. When treating patients with risk factors mentioned above, more frequent outpatient departments should be considered.